Clinical aspects of acute mesenteric ischaemia - Matković Zoran; Maličević Uglješa; Gajić-Bojić Milica; Krivokuća Aleksandra; Đukanović Đorđe; Đekić-Matković Nataša; Aleksić Zoran (Scripta Medica)
Acute mesenteric ischaemia (AMI) is a serious disease with mortality between 50 and 80 %. Oxidative stress plays a major role in the pathophysiology of AMI. AMI should be considered for any acute abdominal pain that requires analgesia with morphine and for which no other obvious aetiology is found. CT is the main diagnostic procedure to confirm the diagnosis of AMI. There is no specific diagnostic biomarker for AMI that can be used in routine practice. AMI is an urgent diagnostic and therapeutic situation. Treatment of AMI includes a protocol combining digestive rest, curative anticoagulant, antiplatelet, antibiotic therapy, arterial revascularisation to salvage viable bowel and resection of necrotic digestive segments. The strategy of revascularisation depends on the mechanism of arterial occlusion, the morphological appearance of the lesions and the indications for exploratory laparotomy. Endovascular and open surgical techniques can be combined and complemented. Open surgical revascularisation is indicated in case of failure or impossibility of endovascular revascularisation and in case of need for laparotomy. Early diagnosis and timely surgical intervention are the cornerstones of modern treatment to reduce the high mortality of AMI. The emergence of endovascular approaches and modern imaging techniques is developing and providing new treatment options. A multidisciplinary approach based on early diagnosis and treatment is necessary.